Impact of multimedia information on bronchoscopy procedure: is it really helpful? - Ersin Gunay (Annals of Thoracic Medicine, 2015)
Aim: In this study, we aimed to investigate the effect of written informed consent and comprehensive multimedia information on the anxiety level of patients, consumption of sedatives, difficulties during bronchoscopy, complications and duration of procedure. Methods: 150 patients undergoing bronchoscopy were included to this study. They were randomized into two groups Multimedia information group (MIG, n = 75) and written-informed consent group (WICG, n = 75)). Signed written informed consent was obtained from all patients. Patients in MIG group watched comprehensive multimedia presentation. State anxiety scores of all patients were evaluated with State and Trait anxiety inventory (STAI-S). Results: STAI-S score of patients in MIG (40.31 ± 8.08) was lower than patients in WICG (44.29 ± 9.62) (P = 0.007). Satisfaction level was higher in MIG (P = 0.001). Statistically higher difficulties during "passage through vocal cords" and "interventions during bronchoscopy" were present in WICG group (P = 0.013 and P = 0.043, respectively). Total midazolam dose during bronchoscopy, and duration of bronchoscopy were statistically lower in MIG patients (P < 0.001 and P = 0.045, respectively). Difficulties during "waiting period", "passage through nasal/oral route", "applications of local anesthesia" and "complication frequency" were similar in both groups. Conclusion: Besides reducing the state anxiety, multimedia information can reduce the dose of sedation, shorten the processing duration and reduce the difficulties during bronchoscopy.